PTPN22 gene polymorphism as a genetic risk factor for primary immune thrombocytopenia in Egyptian children. Issue 9 (2nd September 2021) - hesham, Mervat; Hassan, Tamer; Fawzy, Amal; Mohamed, Noura; Alhejny, Ebtihaj; Fathy, Manar; El Gebaly, Sherief; Zakaria, Marwa
ABSTRACT: Objectives: Several genetic and non-genetic risk factors are implicated in the etiology and pathogenesis of primary immune thrombocytopenia (ITP). Protein tyrosine phosphatase non-receptor 22 gene ( PTPN22 ) plays an important role in regulation of signal transduction through the T-cell receptors. PTPN22 1858 C > T single nucleotide polymorphism was reported to be associated with increased risk of autoimmune diseases. There are very few studies investigating the role of PTPN22 (SNP) 1858 C > T in childhood ITP. Methods: This case-control study was designed for assessing the contribution of PTPN22 1858 C > T polymorphism to the risk of ITP in Egyptian children. Eighty children with newly diagnosed ITP were recruited from pediatric hematology out-patient clinic. Also, eighty age and sex-matched healthy children were enrolled as a control group. PTPN22 1858 C/T SNP gene polymorphism was performed using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). Results: Frequency of PTPN22 1858 C/T genotypes CT, CC, and TT were 32.5, 55, and 12.5% in patients versus 10, 90, and 0% in controls (p < 0.05).TT genotype was significantly associated with higher risk of ITP (OR = 17.8(0.94–333.35), 95% CI, and P = 0.02). Conclusion: PTPN22 gene polymorphism may play a pivotal role in genetic predisposition to ITP and disease progress in Egyptian children.